Natural Carotenoid Pigments of 6 Chlorophyta Freshwater Green Algae Species - Rashidi Othman; Nur Hidayah Noh; Farah Ayuni Mohd Hatta; Mohd Aizat Jamaludin (Journal of Pharmacy and Nutrition Sciences, 2018)
Nowadays, halal products are gaining wider recognition as a new benchmark for safety and quality assurance. As a consequence the commercial development of microalgae is established due to their high value chemicals, for examples, β-carotene, astaxanthin, phycobilin pigments and algal extracts for cosmaceutical products. Therefore, many researchers have gained interest to study the potential of microalgae as new valuable chemicals and other product sources. The aim of the research is to explore new sources of pigments to be used as halal food colorants. This quest is not only directed in finding natural alternatives for synthetic dyes, but also to discover new taxons for the carotenoid production. Thus, there is a solid need to investigate the potential of natural pigments, particularly carotenoids in microalgae to be fully utilised and commercialised especially in halal market, health advantages, food products and dye technology. A total of 6 species was evaluated for quantitative and qualitative carotenoid composition, namely, Chlorella fusca, Chlorella vulgaris, Selenastrum capricornutum, Pandorina morum, Botryococcus sudeticus and Chlorococcum sp. The main carotenoids identified in all species through HPLC analysis were lutein, β-cryptoxanthin and β-carotene. The ratio of these carotenoids varies between species. Lutein was detected substantially higher in Chlorella fusca(69.54±11.29 μg/g DW);β-cryptoxanthin in Pandorina morum species (1.24±0.33 μg/g DW) whereas β-carotene in Chlorella vulgaris (18.42±9.2 ug/g DW). The significant outcome of the research will be new findings of new natural carotenoid pigment sources as potential food colorants and bioactive compounds which can be beneficial to halal health promoting products industry.